2019
DOI: 10.1186/s12894-019-0491-3
|View full text |Cite
|
Sign up to set email alerts
|

Reducing kidney motion: optimizing anesthesia and combining respiratory support for retrograde intrarenal surgery: a pilot study

Abstract: Background One of the greatest challenges presented with RIRS is the potential for movement of the stone within the operative field associated with diaphragm and chest respiratory excursions due to mechanical ventilation. To overcome this challenge, we propose in this pilot study a new general anesthesia technique combining high frequency jet ventilation (HFJV) with small volume mechanical ventilation (SVMV). Data regarding safety, feasibility and surgeons’ impression was assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Lasering and retrieving renal calculi has an added challenge due to respiratory excursions and the associated movement of kidney that occurs during spontaneous breathing. Apnoea is used in ureteroscopy for this purpose to manipulate breathing, reducing respiratory induced renal movement and the literature has suggested that it might be beneficial for clinical outcomes [ 8 , 9 ]. In their paper, Gadzhiev et al showed that reducing renal movement with manipulation of general anaesthetic provided better conditions for stone dusting, and the surgeons using it had a high degree of satisfaction [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lasering and retrieving renal calculi has an added challenge due to respiratory excursions and the associated movement of kidney that occurs during spontaneous breathing. Apnoea is used in ureteroscopy for this purpose to manipulate breathing, reducing respiratory induced renal movement and the literature has suggested that it might be beneficial for clinical outcomes [ 8 , 9 ]. In their paper, Gadzhiev et al showed that reducing renal movement with manipulation of general anaesthetic provided better conditions for stone dusting, and the surgeons using it had a high degree of satisfaction [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, temporary apnoea during the procedure is suggested and often practiced [ 8 ]. A recent study suggests that apnoea is not always mandatory, and the procedure can be safely done with apnoea [ 9 ]. While apnoea can help with the procedure, it can also lead to respiratory complications, longer operative duration and ultimately prolong the length of hospital stay [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation